Effects of kangaroo mother care (KMC) combined with infant touch on physical and neurological development in premature infants - Yang, Huichan; Du, Qiuying; Zhu, Hongbin; Guo, Man; Yang, Qingqing; Ma, Yanfei (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the effects of kangaroo mother care combined with infant touch on the physical and neurological development of premature infants. Method: The randomised controlled trial was at the Maternity and Child Care Centre, Qinhuangdao, China, from January 2023 to January 2024, and comprised premature paediatric inpatients who were randomised into intervention group A and control group B. Those in group B were given routine neonatal intensive care unit care, and were provided with sufficient visual, tactile, auditory and vestibule stimulation and infant touch. Those in group A were additionally given kangaroo mother care. The indicators of physical development, complications during hospitalisation, and monitoring of neurological development were compared between the groups. Data was analysed using SPSS 22. Results: Of the 100 patients, 50(50%) were in group A; 31(62%) boys and 19(38%) girls with mean gestational age 32.1±2.5 weeks. The other 50(50%) patients were in group B; 30(60%) boys and 20(40%) girls with mean gestational age 32.0±2.5 weeks (p>0.05). Post-intervention, body weight, length and head circumference in group A were higher than those in group B (p<0.05). Primitive reflex, passive muscular tension, behavioural ability, general reaction and active muscular tension in group A were all higher than those in group B (p<0.05). The incidence of complications during hospitalisation in group A were slightly lower compared to group B, but the difference was not statistically significant (p>0.05). Conclusion: Kangaroo mother care combined with infant touch significantly improved physical and neurological parameters. Key Words: Kangaroo mother care, Premature infant, Infant touch, Physical development, Neurodevelopment.